2016
DOI: 10.1016/j.pmpp.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Signals that stop the rot: Regulation of secondary metabolite defences in cereals

Abstract: Plants accumulate a vast arsenal of chemically diverse secondary metabolites for defence against pathogens. This review will focus on the signal transduction and regulation of defence secondary metabolite production in five food security cereal crops: maize, rice, wheat, sorghum and oats. Recent research advances in this field have revealed novel processes and chemistry in these monocots that make this a rich field for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 139 publications
(287 reference statements)
0
7
0
Order By: Relevance
“…Functionally, these unique class of flavonoid phytoalexins are initially synthesized in the cytoplasm of epidermal sorghum cells following fungal infection, and accumulate in inclusion bodies. These are translocated toward the site of fungal invasion, where they are then released in active form and kill both the fungus and cells that synthesized them (Poloni and Schirawski, 2014; Meyer et al, 2016). The kinetics and intensity of this response appear to be cultivar-dependent, as reflected by the results in Figure 7C (and Supplementary Figure S9), showing comparative cultivar-related differences in the fold change of apigeninidin and luteolinidin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, these unique class of flavonoid phytoalexins are initially synthesized in the cytoplasm of epidermal sorghum cells following fungal infection, and accumulate in inclusion bodies. These are translocated toward the site of fungal invasion, where they are then released in active form and kill both the fungus and cells that synthesized them (Poloni and Schirawski, 2014; Meyer et al, 2016). The kinetics and intensity of this response appear to be cultivar-dependent, as reflected by the results in Figure 7C (and Supplementary Figure S9), showing comparative cultivar-related differences in the fold change of apigeninidin and luteolinidin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase is one of the most important plant secondary metabolites, and plays an important role in defence against pathogens. Plants have developed extensive mechanisms to perceive chitin elicitors and respond to these stressors by triggering innate defence responses (Meyer et al 30). Interestingly, our GO analysis showed that five and three genes that encoded for chitinase activity were enriched in the NMP vs NM comparison and AMP vs AM comparison respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As for the flavonoids, luteolin and apigenin were the two flavones that were identified and quantified in the sorghum varieties (Dykes et al 2011). Flavonoid phytoalexins, such as 3-deoxyanthocyanidins, are synthesized by sorghum after treatment with jasmonic acid, as an essential component of active defense mechanisms (Du et al 2010;Meyer et al 2016). The 3-deoxyanthocyanins have been identified as orange luteolinidin and the yellow apigeninidin.…”
Section: Herbaceous Energy Cropsmentioning
confidence: 99%